Nilai-Nilai Budaya Sekolah: Studi Kasus Penerapan dan Pengembangan Budaya di SMA Negeri 3 Bantul - Khumayroh, Fasilatun (Al-Misbah (Jurnal Islamic Studies), 2020)
This study was conducted to determine the cultural values applied to a particular school in SMA Negeri 3 Bantul, Yogyakarta. By involving educators and learners, this study was conducted with descriptive approach to the observation of the school environment, observe, and also interview. From research conducted shows that the values of the culture at SMA N 3 Bantul develop according to the collective agreement as a hallmark of the school and implemented in daily activities at school by all parties, both educators, students, and educators.